Growth response of buffaloes treated with oestradiol 17 B - Mahyuddin, Prapti (Indonesian Animal Sciences Society, 1995)
The effect of oestradiol 17 B was tested in 10 buffaloes, weighing approximately 242 kg . They were fed elephant grass ad libitum plus concentrate feed at a rate of 1 % body weight, and were randomly divided into 2 groups of 5, the treated and control groups . The treated group animals were implanted with a long acting oestradiol-silicone rubber on the left ear for 200 days . Oestradiol treated-buffaloes showed a significant increase in liveweight gain (0.89 vs 0 .68 kg/d) and feed conversion ratio (9 .2 vs 11 .2) . Certainly it has a significant economic advantage in using this growth promotant . Key words : Oestradiol, feed conversion ratio, buffalo